UPAYA MENINGKATKAN KECERDASAN VISUAL SPASIAL MELALUI KEGIATAN MELUKIS PADA MEDIA TALENAN KELOMPOK B TK PGRI 3 NGAWI DESA MANGUNHARJO KECAMATAN NGAWI KABUPATEN NGAWI TAHUN PELAJARAN 2021/2022 - Ucik Hidayah Binsa Binsa; Syarifatud Diyanah Diyanah (Kurikula : Jurnal Pendidikan, 2022)
ABSTRACT : Education for early childhood is increasingly popular. Parents increasingly feel the importance of providing education to their children from an early age and compete to provide the best educational facilities for their children. These developments encourage the growth of preschool educational institutions or better known as Kindergarten schools. Visual-spatial intelligence is an intelligence possessed by a person to understand something by visualizing it using the sense of sight in the form of shape, color, and space and the result of that vision is that one of the children can paint it perfectly on a blank paper. The purpose of this study was to determine the visual-spatial intelligence of children in Group B in PGRI 3 Ngawi Kindergarten and efforts to improve visual-spatial intelligence through painting activities on the cutting board of Group B in PGRI 3 Ngawi Kindergarten. The approach used in this research is a qualitative approach where data is collected by interview, observation and documentation methods. Sources of information from this study were the Principal and Teachers of Group B TK PGRI 3 Ngawi. The results of this study are presented in the form of sentences, not in the form of numbers. The data analysis technique used in this research is observation and conclusion drawing. Based on the results of the study, painting activities using cutting boards can improve visual-spatial intelligence in children in TK PGRI 3 Ngawi, this can be seen in the increase in each cycle. Achievement in the pre-cycle percentage is 75% in the undeveloped category and only a few children are in the starting to develop the category. And after taking action during the first cycle, the score for increasing children's visual-spatial intelligence increased to 50% of children starting to develop and 25% of children developing as expected. Furthermore, in the second cycle, which was carried out by carrying out painting activities using a cutting board, there was an increase in children's visual-spatial intelligence to 50% with the category developing as expected and 25% with the category developing very well.